Penggunaan Media Pot Penjumlahan untuk Meningkatkan Kemampuan Menjumlahkan Peserta Didik Kelas IIB MIS Mutiara Aulia - Maysarah Andini; Rora Rizky Andini; Elvira Elvira (Constructivism: Journal of Research in Education, 2024)
Mathematics is a fundamental subject that plays an important role in developing students’ logical, systematic, and critical thinking skills. However, many elementary school students still experience difficulties in understanding basic mathematical concepts, particularly addition operations. These difficulties are often caused by the abstract nature of mathematical concepts and the limited use of concrete learning media during the learning process. Therefore, the use of innovative learning media is needed to help students understand mathematical concepts more effectively. This study aims to describe the use of addition pot media in improving the addition skills of grade IIB students at MIS Mutiara Aulia. This research employed a qualitative approach with a descriptive research design. The subjects of the study were 25 students of class IIB at MIS Mutiara Aulia. Data were collected through observation and documentation techniques during the learning process. The data were analyzed using descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The results of the study show that the use of addition pot media can increase students’ interest and participation in mathematics learning. The colorful and concrete media helps students understand the concept of place value in addition operations more clearly, particularly in addition with regrouping. In addition, the integration of Problem Based Learning encourages students to actively participate in solving problems during the learning process. Therefore, the use of addition pot media can be considered an effective learning strategy to improve students’ addition abilities in elementary school mathematics learning.